2021
DOI: 10.1200/po.20.00220
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor DNA Predicts Pathologic and Clinical Outcomes Following Neoadjuvant Chemoradiation and Surgery for Patients With Locally Advanced Rectal Cancer

Abstract: PURPOSE This study was designed to assess the ability of perioperative circulating tumor DNA (ctDNA) to predict surgical outcome and recurrence following neoadjuvant chemoradiation for locally advanced rectal cancer (LARC). MATERIALS AND METHODS Twenty-nine patients with newly diagnosed LARC treated between January 2014 and February 2018 were enrolled. Patients received long-course neoadjuvant chemoradiation prior to surgery. Plasma ctDNA was collected at baseline, preoperatively, and postoperatively. Next-gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(87 citation statements)
references
References 39 publications
5
82
0
Order By: Relevance
“…In a smaller series, preoperative ctDNA assessments in patients treated with standard neoadjuvant long-course chemoradiation followed by TME did not demonstrate a significant relationship between preoperative ctDNA and pCR, although the correlation was demonstrated between preoperative ctDNA and composite end point markers of surgical outcomes [ 55 ]. Those with postoperative ctDNA-positivity had significantly worse progression-free survival (PFS) than those with negative ctDNA postoperatively (hazard ratio or HR 11.56, p = 0.007) although none with postoperative ctDNA MRD received adjuvant chemotherapy in this cohort.…”
Section: Prediction Of Response To Neoadjuvant Therapy In Locally Advanced Rectal Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In a smaller series, preoperative ctDNA assessments in patients treated with standard neoadjuvant long-course chemoradiation followed by TME did not demonstrate a significant relationship between preoperative ctDNA and pCR, although the correlation was demonstrated between preoperative ctDNA and composite end point markers of surgical outcomes [ 55 ]. Those with postoperative ctDNA-positivity had significantly worse progression-free survival (PFS) than those with negative ctDNA postoperatively (hazard ratio or HR 11.56, p = 0.007) although none with postoperative ctDNA MRD received adjuvant chemotherapy in this cohort.…”
Section: Prediction Of Response To Neoadjuvant Therapy In Locally Advanced Rectal Cancermentioning
confidence: 99%
“…Several groups have noted that ctDNA following neoadjuvant therapy in LARC cannot differentiate between minimal and no residual disease, and instead ctDNA more specifically reflects the presence of systemic disease rather than local minimal disease [ 51 , 58 ]. In this regard, future investigations into the role of ctDNA in the treatment paradigm of LARC may focus on identifying those who may be adequately treated with neoadjuvant chemoradiation and TME alone vs. those who would benefit from intensified TNT upfront based on baseline or pretreatment ctDNA positivity [ 55 ]. Additionally, in those undergoing TNT with chemoradiation first, a post-chemoradiation ctDNA assessment could help guide who should receive chemotherapy rather than move straight to surgery.…”
Section: Future Considerationsmentioning
confidence: 99%
“…Another study including serial plasma collection from 119 LARC patients, who received neoadjuvant chemoradiotherapy showed that mutations of TP53 and APC genes in pre-treatment samples were detected and these mutations were negatively correlated with the response to neoadjuvant chemoradiotherapy [128]. In a recent study, among 29 patients with LARC treated with neoadjuvant chemoradiation, patients with undetectable pre-operative ctDNA had a favorable surgical outcome, and the study confirmed that detectable postoperative ctDNA was associated with worse recurrence-free survival [129]. All these studies evaluated the potential role of ctDNA as a biomarker to predict the treatment outcomes in locally advanced rectal cancer.…”
Section: Other Biomarkersmentioning
confidence: 88%
“…Numerous studies have since confirmed the prognostic validity of ctDNA post-operatively in CRC. 78,[93][94][95][96] In breast cancer, the prognostic ability of ctDNA for identifying RDR was subsequently confirmed across multiple breast cancer subtypes in both independent retrospective and prospective studies that used droplet digital PCR (ddPCR). ddPCR improves on the specificity and sensitivity of PCR by partitioning DNA molecules into droplets, achieving sensitivity to 1 in 10 4 molecules or more and is a scalable method with fewer parameters than NGS panels (Box 1; Figure 2B).…”
Section: Ctdna Detection Methodsmentioning
confidence: 98%